THE 2.40 GA RINGVASSøY MAFIC DYKES, WEST TROMS BASEMENT COMPLEX, NORWAY: THE CONCLUDING ACT OF EARLY PALAEOPROTEROZOIC CONTINENTAL BREAKUP - Kullerud K.; Skjerlie K.P.; Corfu F.; de la Rosa J.D. (My University, 2006)
A north to northwest trending mafic dyke swarm of gabbronoritic and gabbroic composition makes up a significant part of the Archean basement on the island of Ringvassøy in northern Norway. U-Pb geochronology of zircon and baddeleyite in a gabbronorite provides an age of emplacement of 2403 ± 3 Ma. Metamict zircon in a plagioclase phyric dyke yield data that are discordant but consistent with the age of the gabbronoritic dyke. Titanite indicates a metamorphic overprint at 1768 ± 4 Ma. The two types of dyke show some distinct chemical characteristics. They are both tholeiitic, enriched in LREEs and LILE elements but depleted in HFS elements including Nb. Their Nd isotopic composition yields εNd values of -1.5 to -1.8 for gabbronorites and -0.4 to +1.3 for the plagioclase phyric dykes. The chemical and isotopic constraints are typical of continental basalts. The Ringvassøy mafic dykes correlate broadly with a global Palaeoproterozoic magmatic event that formed extensive bimodal intrusive and extrusive suites in most Archaean cratons, including the northeastern Fennoscandian Shield. In detail, the 2403 ± 3 Ma Ringvassøy dykes postdated most episodes of magmatism at this time. On the regional scale there is a distinct trend from a 2505-2490 Ma suite present in the Kola Peninsula, over a second 2460-2440 Ma suite present both in Kola and further south in Karelia, to the 2403 Ma dykes on Ringvassøy. This variation suggests that the locus of maximum extension and magmatic activity may have been shifting with time. © 2006 Elsevier B.V. All rights reserved.
Keywords: FENNOSCANDIAN SHIELD; MAFIC DYKES; PALAEOPROTEROZOIC; WEST TROMS BASEMENT COMPLEX; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская